The role of fluid intelligence and socioeconomic status on reading development in students with intellectual disability: The mediated role of early literacy skills and moderation by socioeconomic status - Lisa Palmqvist; Mikael Heimann; Jenny Samuelsson; Gunilla Thunberg; Monica Reichenberg; Mats Lundälv; Emil Holmer (Acta Psychologica, 2025)
Reading is essential for academic success and societal participation, yet many individuals with intellectual disability struggle with reading. Purpose: This is the first study to investigate how fluid intelligence and socioeconomic status (SES) influence reading ability in beginning readers with intellectual disability, focusing on the mediating role of early literacy skills while testing the possible moderated mediation of SES. Method: Using structural equation modelling (SEM), we analyzed data from 135 beginning readers with intellectual disability (mean age 13.7 years) attending Swedish compulsory schools for students with intellectual disability. Findings: The results showed that the effect of fluid intelligence on reading ability is mediated via early literacy skills. Furthermore, the results show that this mediation was stronger in students with higher SES compared to those with lower SES. This study provides new results suggesting that supportive environmental contexts provided by higher SES might amplify the benefits of fluid intelligence on reading outcomes. Despite the cross-sectional nature of the data, the findings underscore the importance of early literacy skills and the broader socio-economic context in reading ability for students with intellectual disability. Educational interventions should prioritize enhancing early literacy skills and might need to consider socio-economic factors to effectively support reading development. Future research should explore additional cognitive, linguistic, and environmental factors, utilizing longitudinal designs to confirm these findings and inform tailored educational strategies.